2018
DOI: 10.2147/copd.s157953
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative computed tomography features and clinical manifestations associated with the extent of bronchiectasis in patients with moderate-to-severe COPD

Abstract: BackgroundFew studies have investigated the quantitative computed tomography (CT) features associated with the severity of bronchiectasis in COPD patients. The purpose of this study was to identify the quantitative CT features and clinical values to determine the extent of bronchiectasis in moderate-to-severe COPD patients.MethodsA total of 127 moderate-to-severe COPD patients were selected from the cohort of COPD in Dusty Areas (CODA). The study subjects were classified into three groups according to the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 42 publications
0
16
1
Order By: Relevance
“…Of all of these, 14 duplicates were removed. After reviewing the titles and abstracts, 76 full-text articles were identified and reviewed, and, finally, 18 studies 11,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were included in this systematic review and meta-analysis. The flow diagram of article selection according to the PRISMA guideline 13 is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of all of these, 14 duplicates were removed. After reviewing the titles and abstracts, 76 full-text articles were identified and reviewed, and, finally, 18 studies 11,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were included in this systematic review and meta-analysis. The flow diagram of article selection according to the PRISMA guideline 13 is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 415,257 subjects with COPD from 18 observational studies 11,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were eligible for this meta-analysis, and bronchiectasis was present in 25,929 subjects (6.24%). The sample size ranged from 54 to 386,646, and 6 studies [17][18]20,22,25,33 had a small population (N < 100).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects include those having or not having airflow limitations based on spirometry. The protocols of data collection in the CODA cohort were previously described in detail [ 23 25 ]. In brief, we obtained data on demographic characteristics, medical history, and environmental exposures from participant questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…COPD often coexists with other diseases (comorbidities) which may have significant impacts on prognosis of COPD patients. With increasing use of high-resolution computed tomography (HRCT) in assessment of COPD, a high prevalence of previously undiagnosed bronchiectasis was found in COPD patients, ranging from 8.1-69% [7][8][9][10][11][12][13][14][15][16][17][18][19]. Some previous studies suggested the presence of bronchiectasis predicted worse outcome of COPD patients [9-11, 13, 15, 20].Therefore, bronchiectasis was proposed as one of COPD comorbidities by 2014 global initiative for chronic obstructive lung disease (GOLD).…”
mentioning
confidence: 99%